2022
DOI: 10.1038/s41467-022-32344-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis of inverse vulcanized polymers

Abstract: Inverse vulcanization, a sustainable platform, can transform sulfur, an industrial by-product, into polymers with broad promising applications such as heavy metal capture, electrochemistry and antimicrobials. However, the process usually requires high temperatures (≥159 °C), and the crosslinkers needed to stabilize the sulfur are therefore limited to high-boiling-point monomers only. Here, we report an alternative route for inverse vulcanization—mechanochemical synthesis, with advantages of mild conditions (ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…[29][30][31] A wide range of innovative, lower-temperature processing and recycling techniques have also been explored. 29,[32][33][34][35][36] Sustainability of HSMs has been further improved by using biologically-produced olen comonomers, such as lignin derivatives, 5,6,8,9 cellulose derivatives, 37,38 starch, [39][40][41][42] raw lignocellulosic biomass, 43,44 fatty acids, [45][46][47] triglycerides, 48,49 terpenoids, 38,50 and amino acid derivatives. 51 Miscibility issues for hydrophilic olen sources during the HSM-forming reaction has been observed in some of these studies and could be addressed by using extended reaction times, adding compatibilizing agents/catalysts, or mechanochemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] A wide range of innovative, lower-temperature processing and recycling techniques have also been explored. 29,[32][33][34][35][36] Sustainability of HSMs has been further improved by using biologically-produced olen comonomers, such as lignin derivatives, 5,6,8,9 cellulose derivatives, 37,38 starch, [39][40][41][42] raw lignocellulosic biomass, 43,44 fatty acids, [45][46][47] triglycerides, 48,49 terpenoids, 38,50 and amino acid derivatives. 51 Miscibility issues for hydrophilic olen sources during the HSM-forming reaction has been observed in some of these studies and could be addressed by using extended reaction times, adding compatibilizing agents/catalysts, or mechanochemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 Since inverse vulcanization was created in 2013, 4 new crosslinkers for synthesis, and interesting intrinsic properties and unexpected applications of relevant materials have been extensively studied. Plenty of research has demonstrated that inverse vulcanized polymers have unique properties which traditional carbon-based polymers lack, such as affinity for metal, 5,6,7,8 chemically dynamic property, 9,10,11,12 ultrahigh refractive index (n>1.8) 13,14,15 et al, and they have been proved that they are able to be used in many promising applicable fields, such as antimicrobial material, 16,17 water remediation, 5,7,8,18 Li-S battery, 19,20,21 infrared thermal imaging, 22,23,24 optics throughout visible range, 15,25 and self-healing materials 12,26,27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…2 Very recently, a mechanochemical synthesis was suggested as an alternative route to inverse vulcanization. 32 Transient optical absorption measurements show that sulfur polymerization can be also achieved below 159 °C by means of photoexcitation using a laser illumination with an intensity larger than 0.21 mJ/cm 2 , although the decomposition of S 8 rings can be observed at weaker laser illumination. 33,34 understanding of the chemical and physical properties of elemental sulfur, S 8, is an important task.…”
mentioning
confidence: 99%
“…Currently, a widely used approach to develop stable sulfur polymers is to link the sulfur chains, generated upon heating above the floor temperature of sulfur, with organic comonomers, an approach referred to as inverse vulcanization . Very recently, a mechanochemical synthesis was suggested as an alternative route to inverse vulcanization . Transient optical absorption measurements show that sulfur polymerization can be also achieved below 159 °C by means of photoexcitation using a laser illumination with an intensity larger than 0.21 mJ/cm 2 , although the decomposition of S 8 rings can be observed at weaker laser illumination. , Thus, in this context, gaining a better understanding of the chemical and physical properties of elemental sulfur, S 8, is an important task.…”
mentioning
confidence: 99%